2014
DOI: 10.1002/dmrr.2588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lixisenatide in elderly ( ≥65 years old) and very elderly ( ≥75 years old) patients with type 2 diabetes: an analysis from the GetGoal phase III programme

Abstract: Background The objective of this article is to evaluate the pharmacokinetics, efficacy and safety of lixisenatide (subcutaneous injection) in elderly (≥65 years old) and very elderly (≥75 years old) patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 36 publications
3
43
0
3
Order By: Relevance
“…Subgroup analyses by age groups are the most commonly reported: analyses for liraglutide, exenatide twice daily, exenatide once weekly, and lixisenatide have been published [11,[13][14][15]. In this analysis of dulaglutide studies, elderly patients (≥65 years) had significantly greater reductions in HbA1c, significantly higher incidence of hypoglycemia, and significantly smaller increases in pulse rate compared to younger patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subgroup analyses by age groups are the most commonly reported: analyses for liraglutide, exenatide twice daily, exenatide once weekly, and lixisenatide have been published [11,[13][14][15]. In this analysis of dulaglutide studies, elderly patients (≥65 years) had significantly greater reductions in HbA1c, significantly higher incidence of hypoglycemia, and significantly smaller increases in pulse rate compared to younger patients.…”
Section: Discussionmentioning
confidence: 96%
“…This is the first analysis of dulaglutide across subgroups; these stratification factors have also been used in previous pooled subgroup analyses for other GLP-1 receptor agonists, such as liraglutide [11,12], exenatide twice daily [13], exenatide once weekly [14], and lixisenatide [15].…”
Section: Discussionmentioning
confidence: 99%
“…In two separate meta-analyses of five randomized controlled trials from the GetGoal phase III clinical trial program, lixisenatide plus OADs showed improved glycemic control in older patients inadequately controlled with OADs compared with placebo plus OADs and was effective and well tolerated in older ($65 years) and very old ($75 years) patients with type 2 diabetes (21,22).…”
mentioning
confidence: 99%
“…Во всех исследованиях наблюдалось со-поставимое снижение уровня HbA 1c у пациентов в возрасте <65 лет и пожилого возраста. Частота симптоматической гипогликемии варьировала в за-висимости от фонового лечения и была сопоставима между ликсисенатидом и плацебо; не наблюдалось значимых различий между молодыми пациентами и лицами в возрасте от 65 до 75 лет [52].…”
Section: лечение сд2 у пожилых пациентовunclassified
“…Важно напомнить, что 80-летние пациенты имеют большую распро-страненность когнитивных нарушений, инвалидно-сти, почечной и печеночной дисфункции, остеопо-роза по сравнению с менее пожилыми субъектами. Обзор, представленный A. M. Abbatecola (2015), постулирует необходимость умеренного гликеми-ческого контроля (уровни НbA1 с 7-8%) у пациентов пожилого возраста в целях поддержания баланса между терапией сопутствующих заболеваний и ка-чеством жизни [4].…”
unclassified